2011
DOI: 10.1016/j.ccr.2011.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of the Tumor Suppressor GRHL3 by a miR-21-Dependent Proto-Oncogenic Network Results in PTEN Loss and Tumorigenesis

Abstract: Despite its prevalence, the molecular basis of squamous cell carcinoma (SCC) remains poorly understood. Here, we identify the developmental transcription factor Grhl3 as a potent tumor suppressor of SCC in mice, and demonstrate that targeting of Grhl3 by a miR-21-dependent proto-oncogenic network underpins SCC in humans. Deletion of Grhl3 in adult epidermis evokes loss of expression of PTEN, a direct GRHL3 target, resulting in aggressive SCC induced by activation of PI3K/AKT/mTOR signaling. Restoration of Pten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
281
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 213 publications
(304 citation statements)
references
References 71 publications
22
281
1
Order By: Relevance
“…Deletion of Grhl3 at P1 does not lead to barrier defect nor to death from dehydration. This suggests that although Grhl3 is essential for barrier establishment, it is not required for crucial maintenance of the epithelium [48]. Recent data indicated that another Grhl gene, Grhl1, is compensating for the loss of Grhl3 in adulthood, accounting for the ability of these conditional KO (cKO) mice to maintain an intact skin barrier [49].…”
Section: Grhl3 Is Expressed In the Differentiated Supra-basal Compartmentioning
confidence: 99%
See 4 more Smart Citations
“…Deletion of Grhl3 at P1 does not lead to barrier defect nor to death from dehydration. This suggests that although Grhl3 is essential for barrier establishment, it is not required for crucial maintenance of the epithelium [48]. Recent data indicated that another Grhl gene, Grhl1, is compensating for the loss of Grhl3 in adulthood, accounting for the ability of these conditional KO (cKO) mice to maintain an intact skin barrier [49].…”
Section: Grhl3 Is Expressed In the Differentiated Supra-basal Compartmentioning
confidence: 99%
“…Furthermore, the mitotic cells that usually reside towards the basal epidermal layer, where the HF and IFE SCs as well as the TA cells are found, become increasingly prominent in the suprabasal layers, promoting a tumourigenic environment [48]. Pseudo-tumours form from these supra-basal cells when cultured in vitro, demonstrating their potential to become carcinogenic given the right microenvironment [48].…”
Section: Grhl3 Is Expressed In the Differentiated Supra-basal Compartmentioning
confidence: 99%
See 3 more Smart Citations